Catalytic Chemical Vapor Deposition Synthesis of Carbon Aerogels of High-Surface Area and Porosity - Armando Peña; Julio Puerta; Aimé Guerrero; Edgar Cañizales; Joaquín L. Brito (Journal of Nanotechnology)
In this work carbon aerogels were synthesized by catalytic chemical vapor deposition method (CCVD). Ferrocene were employed as a source both of catalytic material (Fe) and of carbon. Gaseous hydrogen and argon were used as reductant and carrier gas, respectively. The products of reaction were collected over alumina. The morphology and textural properties of the soot produced in the reaction chamber were investigated using Scanning Electron Microscopy, High-Resolution Transmission Electron Microscopy, X-ray photoelectron spectroscopy, and N2 physisorption (BET and BHJ methods). After the evaluation of the porous structure of the synthesized products, 780 ± 20 m2/g of SBET and 0.55 ± 0.02 cm3/g of VBJH were found. The presence of iron carbide and the partial oxidation of carbon nanostructures were revealed by XPS.